THERAPY OF GRAVES’ DISEASE WITH SODIUM IODIDE-131 - I Wayan Hartadi Noor; Made Ratna Saraswati (E-Jurnal Medika Udayana, 2013)
Graves’ disease is the most common form of thyrotoxicosis, with a peak incidence in the 20-40 year of age group. Females are involved about five times more commonly than male. The easiest sign to recognize patients with Graves’ disease is the present of Graves’ ophthalmopathy. The diagnosis of Graves’ disease may sometimes base only on a physical examination and a medical history. Diffuse thyroid enlargement and sign of thyrotoxicosis, mainly ophthalmopathy and to lesser extent dermopathy, usually adequate for diagnosis. TSH test combined with FT4 test is usually the first laboratory test performs in these patients. The patients suffered Graves’ disease can be treated with antithyroid drug therapy or undergo subtotal Thyroidectomy. Another therapy is by using sodium iodide-131, where this therapy has advantages including easy administration, effectiveness, low expense, and absence of pain.